Cooperando para apreender : as trocas cognitivas em situação de jogo na aprendizagem de língua inglesa - Vieira, Ethieli (2015)
Increasingly, studying a foreign language is essential for interaction in a globalized world. From this assumption the English language has been present in Brazilian basic school as a compulsory subject of modern foreign language starting in the third cycle of elementary school. But inside the classroom such requirement is not a guarantee that the language teaching is free of specificities in relation to learning. One of these specificities is the coexistence, in a particular class, where students are in different levels of knowledge about English language. In this context, this study had the general objective of analyzing how cooperation and exotopy / surplus of vision burst upon the scene when students experience situations potentially didactic interactive and dialogic, with views to learning the English language. This study is characterized as a intervention research of a qualitative approach, performed by running ten workshops of games using the English language with ten students from grade six of a private school in Passo Fundo, RS. The workshops were recorded through videotaping and audio, and direct observation of the researcher. The generated data was subjected to treatment second procedure of content analysis. The data analysis was based on the theoretical support of Piaget (1973, 1994, 1998, 2012, 2014), Bakhtin/Voloshinov (1997) and Bakhtin (2011), as well as contemporary authors who interpret their works. Categories were operated as cooperation, mutual and unilateral respect, grouping operations, interaction, enunciated/enunciation, active responsive understanding, exotopy and also surplus of vision. It was concluded that for these concepts come into play and boost language learning, some factors are needed, such as mutual respect and reciprocity. When these elements are present they provide students operate in common and solve the activities proposed, through discussion and mutual control of arguments. This cooperative scenario allows students to expose their surplus of vision, both regarding the language knowledge, and in regard to the game strategies, thus enable the construction of new knowledge of the English language. Furthermore, we conclude that the organization and methodology of the game are essential to allow moments of interaction and hence qualified cognitive changes